INTEGRATIVE OMICS APPROACH IN BREAST CANCER MANAGEMENT - Hiljadnikova-Bajro, Marija; Djokoski, F. (https://lm4ms.gr/images/LM4MS_ABSTRACTS.pdf, 2022)
INTEGRATIVE OMICS APPROACH IN BREAST CANCER MANAGEMENT Marija Hiljadnikova-Bajro, Filip Djokoski Institute for Applied Biochemistry, Faculty of Pharmacy, Ss. Cyril and Methodius University in Skopje, Majka Tereza 47, Skopje, Republic of North Macedonia Introduction As the most frequent malignancy and a leading cause of cancer death among women worldwide, breast cancer (BC) remains a huge challenge for multidisciplinary approaches in advancement of the diagnostic and treatment strategies. Aim To evaluate and highlight the potential of integrative omics approach in BC management. Methodology Comprehensive literature survey. Results The advanced genomic methodologies like next-generation sequencing, complemented with the novel insights in transcriptomics, epigenomics, proteomics, metabolomics and microbiomics, have set the scene for large-scale research aimed at discovery and clinical application of novel, highly specific laboratory markers to enable early diagnosis, precise prognosis and classification, timely and personalized treatment, effective monitoring or design of a targeted pharmacotherapy. Apart from breast tissue, specimens like urine, tumor interstitial fluid, blood, serum or plasma, saliva and the nipple aspirate fluid are frequently used as sources of biomarkers in clinical research involving various ‘omics approaches. The set of laboratory markers currently implemented in clinical practice, including CA 15-3, CEA, ER-, PR-, HER2-expression, BRCA1and 2 mutations, is expected to be supplemented with novel promising markers like microRNA molecules (oncomiR and TS-miRNAs), circulating RNAs, circulating tumor DNA, circulating cell free DNA, CA27.29 molecules, but potential is also identified for EZH2, GP88, Cyclin-E, B-Myb, Twist, DMP1β, RB1, novelty discovered hub genes like CENPL, ISG20L2, LSM4, MRPL3, and a number of metabolites, amino acids and lipids. The available ‘omics databases like PRIDE, COSMIC, GENIE, TCGA, CPTAC, GXB, GEO, HUPO and TACCO; the molecular assays including OncotypeDx and MammaPrint; cancer metabolic biomarker database (CMBD); the Human OncoBiome Database; the AURORA program, the BC epigenomics track hub, have aided substantially the integration of results and their in silico analysis, data access to independent research groups enabling evaluation of previously detected or identification of novel markers with clinical relevance including: genes, proteins, metabolites, microbiota-constituents. Conclusion The novel ‘omics technologies have dramatically changed our understanding of the mechanisms underlying cancer. Their integrative application holds huge potential in characterization of BC heterogeneity in a therapeutically meaningful way as well as identification of potential biomarkers to be used as hallmarks of the disease or targets for personalized drug design.
Keywords: Breast cancer, genomics, epigenomics, transcriptomics, proteomics, microbiomics